The Role of Animal Traction Technology in enhancing Production for Small Scale Farmers in Sierra Leone - Turay, Samba Prince; Jalloh, Mohamed Tejan; Bandabla, Tamba; Kassoh, Fallah Samuel; S. Yillah, Dauda (International Journal of Environment, Agriculture and Biotechnology, 2022)
This paper summarises the results of a base line survey conducted in 2019 and gives an overview of the current status of animal traction in the country. The study assessed the socio-economic characteristics of household heads utilizing the technology, the application of animal power and its associated opportunities and constraints. A total of 130 households were targeted and data were collected through the administration of structured questionnaires, key informant interviews, and focus group discussions. Majority (99.2%) of household heads using this technology were males. The ethnic groups mostly involved in animal traction were Madingos (18.6%), with the least being the Shebro tribe (1.6%). Farming was the main source of income for about (96.1%) of the respondents. The level of awareness of the technology was very high and most (71.3%) of the household heads became aware about traction from other farmers. Cattle was the sole draught animal used and was mainly sourced through purchase (69%). In the selection of oxen for traction, bulls of medium sizes and aged 2 years were the most preferred. Household heads possessed an average of 9.73 years of experience in animal traction and owned at least a farm site with mean sizes of 6.93 acres. Animal power was mostly preferred over traction due to ease of management, cost effectiveness and its potential to give higher crop yields. Traction services was estimated as readily available by (32.6%) of the farmers, with (10.1%) citing the service as not readily available. Animal traction was used solely for agricultural purposes and ploughing was the most common activity. A set of oxen was reported to plough about 1.4 acres within 5.1 hours with weekly and annual work cycles of 5.2 days and 5.3 months respectively. Operators of work oxen were mostly males with few adolescent boys and rarely women. (77.5%) of household heads owned implements with about (22.5%) not owning implements. Majority (80.6%) of the implements were imported with (19.4%) locally fabricated. In conclusion, the awareness and use of animal traction for agricultural purposes was quite high and due to its numerous advantages is highly recommended for small scale farmers.